Homophobic beliefs and attitudes among mid-adolescent boys: exploring the ideas of hybrid masculinities - Exner-Cortens, Deinera; Claussen, Caroline; Jenney, Angelique; Vijayan, Vineetha Warriyar Kodalore (Frontiers in Sociology, 2024)
Introduction: Homophobia is well-documented as key to social regulation of masculine behavior and practices in Western settings. Yet, empirical data from a number of Western settings has shown a decline in overt homophobic attitudes in the past decade, leading some to suggest that the nature of masculinities is also changing. However, theorizing on the changing nature of masculinities among adolescents has received limited quantitative attention. Research is needed to better understand shifts in adolescent masculinities in contemporary Western settings. Methods: In this paper, we investigate the application of one newer approach to explore masculinities in context – hybrid masculinities – in a sample of cisgender, heterosexual, mid-adolescent boys in one province in Western Canada (N = 873, mean age (SD) = 14.39 (0.37)). Data were collected from nine cohorts of grade 9 youth over a 10-year period (2013-2022) as part of the baseline survey of an ongoing evaluation of a gender-transformative healthy relationships program. Results and Discussion: We hypothesized that if the ideas of hybrid masculinities held in our sample, we would find that overt homophobic attitudes and adherence to related patriarchal norms (e.g., avoidance of femininity) would decline over this period, but that the use of homophobic name-calling would remain differentiated in terms of to whom it was directed (e.g., a friend, someone they thought was gay). We did find a significant decline in homophobic attitudes and norms related to emotional restriction and avoidance of femininity over the 10-year period, and also found that homophobic name-calling remained differentiated, with significantly higher name-calling towards a friend than towards someone the youth thought was gay. Thus, our hypotheses were supported. We discuss the implications of our findings for future theory and research on understanding adolescent masculinities in context.